1989
DOI: 10.1111/j.1399-302x.1989.tb00246.x
|View full text |Cite
|
Sign up to set email alerts
|

The capacity of subgingival microbiotas to produce volatile sulfur compounds in human serum

Abstract: Hydrogen sulfide is formed by the subgingival microbiotas of periodontal pockets. The capacity of these microbiotas to form various volatile sulfur compounds in human serum was studied. Bacterial samples from nine deep periodontal pockets were incubated for 7 days in human serum and the amounts of volatile sulfur compounds and the degradation of serum proteins were determined. Hydrogen sulfide was the predominant volatile sulfur compound, but also methyl mercaptan was formed in significant amounts. Only traces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0
9

Year Published

1995
1995
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(102 citation statements)
references
References 31 publications
1
92
0
9
Order By: Relevance
“…Further, H2S in hibits myeloperoxidase and catalase (9). The high concentration of H2S in peri odontal pockets (21,24) may well orig inate from the degradation of cysteine by oral microbiota (25,26). We suggest that the number of sulfate-reducing bacteria in periodontal pockets and also their contribution to H2S produc tion are low due to the limited availabil ity of the energy source sulfate in the environment.…”
Section: Discussion Tmentioning
confidence: 98%
“…Further, H2S in hibits myeloperoxidase and catalase (9). The high concentration of H2S in peri odontal pockets (21,24) may well orig inate from the degradation of cysteine by oral microbiota (25,26). We suggest that the number of sulfate-reducing bacteria in periodontal pockets and also their contribution to H2S produc tion are low due to the limited availabil ity of the energy source sulfate in the environment.…”
Section: Discussion Tmentioning
confidence: 98%
“…27 These bacteria proteolyse the sulphur-containing amino acids from the proteins in the saliva, shed epithelium, food debris, gingival crevicular fluid, interdental plaque, and postnasal drip thereby releasing the VSCs. 28 Bacterial strains forming large amounts of H 2 S from L-cysteine were found in the genera Peptostreptococcus, Eubacterium, Salenomonas, Centipeda, Bacteroides, and Fusobacterium, and CH 3 SH from L-methionine was formed by some members of the genera Fusobacterium, Bacteroides, Porphyromonas, and Eubacterium . 29 Awano et al detected the presence of T. forsythensis, P. gingivalis, Aggregatibacter actinomycetemcomitans, and P. intermedia by PCR in the saliva of patients complaining of halitosis.…”
Section: Bacteria / Microorganismsmentioning
confidence: 99%
“…For instance, hydrogen sulfide is derived from desulfuration of cysteine and methyl mercaptan from desulfuration of methionine. It has been demonstrated that innumerous oral bacterial species, including candidate endodontic pathogens, are able to form volatile sulfur compounds (79,80 (79). Volatile sulfur compounds are expected to be formed by endodontic bacteria from the free sulfur amino acids present in tissue fluids or exudate that penetrate in the root canal.…”
Section: Metabolic End-productsmentioning
confidence: 99%